Factor affecting student of environmental conservation concern - Nur Aidar; . Rahmayani (Syiah Kuala University, 2013)
This study aims to determine the factors that affect student concerns to the environment. The logistic fuction is used in this study, where 110 respondents chosen randomly. The result shown that only motivation factor is significant to influence student to awareness environmental, where as the levels of education is statically not significant. Conclusion of the study showed higher levels of education and motivation, then student is more concerned about the environment. Furthermore, if motivation increase by one percent, the probability students to awareness environment increase by 784,18 percent. Thus need to be given counseling and motivation for student to make them more concerned about the preservation of an environment